Application of transparent self-cleaning coating for photovoltaic panel: a review. (June 2022) - Syafiq, Amirul; Balakrishnan, Vengadaesvaran; Ali, Mohd Syukri; Dhoble, Sanjay J; Rahim, Nasrudin Abd; Omar, Azimah; Bakar, Ab Halim Abu
Graphical abstract: Self-cleaning photovoltaic (PV) panel. Abstract : This review article focuses on the recent development of transparent self-cleaning coating based on the glass panel application especially for the photovoltaic (PV) panel industry, automobile industry, and building glass industry. The study on wettability revolutionized the development of self-cleaning property that leads to higher demand from industries. The usage of mechanical and robotic cleaners for cleaning purposes seems impractical since it causes damages on the glass surface, limited electric generation during heavy rain, and require costly equipment. Therefore, in this review article, a brief study on the application of the transparent self-cleaning coating is thoroughly explained as the basic principle for the future developments of self-cleaning coating related to industry demand.